Rearing background and exposure environment together explain higher survival of aquaculture fish during a bacterial outbreak. Issue 7 (2nd May 2019) - Räihä, Ville; Sundberg, Lotta‐Riina; Ashrafi, Roghaieh; Hyvärinen, Pekka; Karvonen, Anssi
Abstract: Parasitic diseases represent one of the greatest challenges for aquaculture worldwide and there is an increasing emphasis on ecological solutions to prevent infections. One proposed solution is enriched rearing, where traditional stimulus‐poor rearing tanks are equipped with different types of structures to increase habitat complexity. Such spatial enrichment is known to increase survival of fish during parasite epidemics, but the underlying mechanisms are still unclear. We studied whether enriched rearing affected infection of an important fish pathogen Flavobacterium columnare in young Atlantic salmon ( Salmo salar ) and sea‐migrating brown trout ( Salmo trutta ). First, we used natural bacterial exposures and multiple fish populations in a common garden experiment to address the role of host genetic background in effects of enriched rearing. Second, fish from standard and enriched rearing were experimentally exposed to controlled bacterial doses in standard and enriched environments in a full factorial design to explore the relative roles of rearing background and environment of exposure on survival of fish. Enriched rearing significantly increased survival of fish during the natural bacterial outbreak. This effect was also fairly consistent and observed in eight of the ten fish populations. In the controlled exposure, fish exposed in enriched environment had higher survival regardless of their rearing background, suggesting a stronger impact of the environment on the disease progression. Additionally, the survival in the enriched environment was the highest among the fish of enriched rearing background, supporting the idea of their higher resistance. Synthesis and applications . Our study suggests that the enhanced survival of fish in enriched rearing is a result of a combined effect of the environment and improved fish condition and, to a lesser degree, from host genetic background. This has important implications for when and how environmental enrichment should be applied. Overall, these results indicate that environmental enrichment has the potential to improve survival of fish during parasitic epidemics and thus reduce use of antibiotics in aquaculture. Abstract : Our study suggests that the enhanced survival of fish in enriched rearing is a result of a combined effect of the environment and improved fish condition and, to a lesser degree, from host genetic background. This has important implications for when and how environmental enrichment should be applied. Overall, these results indicate that environmental enrichment has the potential to improve survival of fish during parasitic epidemics and thus reduce use of antibiotics in aquaculture.